Natural and Experimental Infection of Campylobacter cryaerophila in Rainbow Trout : Gross Pathology, Bacteriology, Clinical Pathology and Chemotherapy - Aydın, Seyit; Gültepe, Nejdet; Yıldız, Harun (The Japanese Society of Fish Pathology, 35 (3), 117-123,2000.9, 2000)
Campylobacter cryaerophila was isolated from naturally infected rainbow trout (Oncorhynchus mykiss), and its pathogenicity was tested by intramuscular injection using 1-yearold rainbow trout and scattered mirror carp (Cyprinus carpio). C. cryaerophila did not induce experimental infection in scattered mirror carp. Natural and experimental infections caused mortalities in rainbow trout with gross clinical abnormalities such as exophthalmia, damage of liver, bloody kidney and haemorrhagic heart and swollen intestine. Glucose, cholesterol, triglyceride and haematocrit levels in blood of both naturally and experimentally infected fish were significantly decreased as compared to healthy fish. Significant decreases were observed in the serum glutamate oxatacetate transaminase level of experimentally infected fish and serum total protein value of naturally infected fish. Albumin levels of serum were not significantly different among the three treatments. Sensitivities of three isolates of C. cryaerophila against 51 chemotherapeutants were determined. Minimum inhibitory concentrations of formalin and enrofloxacin to the isolates were between 3.5—4.5 uL/mL and 0.025—1 uL/mL, respectively. Oral applications of enrofloxacin after bath disinfections with formalin controlled the natural infections.
Keywords: Camplobacter cryaerophila, rainbow trout, blood chemistry, haematocrit, chemothrapy, enrofloxacin